Karakterisitik Fisiko-Kimia dan Sensori Bakso Ikan Gabus (Channa striata) dengan Penambahan Genjer (Limnocharis flava) - Ni Made Pratiwi; Indah Widiastuti; Ace Baehaki (Universitas Sriwijaya, 2016)
The purposes of this research were investigated the physicochemical and sensory characteristics of snakehead fish ball with yellow velvetleaf addition. The research was conducted on January until March 2016. The research method was used randomized block design (RBD). The treatments were 0%, 5%, 10%, and 15% of yellow velvetleaf addition. The parameters of this research was chemical analysis such as water content, ash content, protein content, lipid content, carbohydrate content, and fiber; physical analysis were elasticity; colour and sensoric analysis (texture, taste, colour and aroma). The results showed that treatment gave significant effect on ash content, water content, ash content, protein content, and fiber content; lightness and sensoric analysis (taste and colour), but there were no effect to lipid content, carbohydrate content and elasticity, chrome and hue. The concentration of water, ash, protein, and fiber were 63.32%-69.27%, 1.21%-6.44%, 14.69%-20.61%, 0.93%-5.65% respectively. The lightness of this fish ball were54.23%-6676%. Color sensory analysis of fish ball were 3.28-3.86 and taste were 3.17-3.36. The best treatments were A2 (10% yellow velvetleaf addition).